After the unveiling of a plaque at the former headquarters of the East London Federation of Suffragettes. F.l.t.r.: Watson, Isolani, Ayling and Benn - Morrad, Annie,
After the unveiling of a plaque at the former headquarters of the East London Federation of Suffragettes. F.l.t.r.: Watson, Isolani, Ayling and Benn.